Study protocol for a pilot high-intensity interval training intervention in inpatient mental health settings: a two-part study using a randomised controlled trial and naturalistic study design - Rebecca Martland (BMC, 2021)
Abstract Background Severe mental illnesses (SMI), including schizophrenia spectrum disorder, bipolar disorder and major depressive disorder, are associated with physical health comorbidities and premature mortality. Physical activity and structured exercise have a beneficial impact on cardiometabolic risk and ameliorate mental health symptomology and cognition. This protocol describes a feasibility study for a high-intensity interval training (HIIT) intervention among inpatients with SMI, to improve their physical and mental health. Methods The feasibility study follows a two-part design owing to COVID-19-related adaptations to project design: (a) a non-blinded randomised controlled trial (RCT) of 12 weeks of bicycle-based HIIT, delivered twice weekly in a face-to-face, one-to-one setting, compared to treatment as usual (TAU) and (b) a naturalistic study of inpatient HIIT; eligible participants will be invited to two sessions of HIIT per week, delivered by the research team remotely or in person. Additionally, participants in the naturalistic study may use the bike to conduct self-directed sessions of their chosen length and intensity. We will measure the feasibility and acceptability of the HIIT intervention as primary outcomes, alongside secondary and tertiary outcomes evaluating the physical, mental and cognitive effects of HIIT. The study aims to recruit 40 patients to the RCT and 6–8 patients to the naturalistic design. Discussion Exercise is a modifiable lifestyle barrier that can reverse cardiometabolic disease risk. If HIIT is found to be feasible and acceptable in inpatients with SMI, there would be scope for large-scale work to evaluate the clinical, cost and implementation effectiveness of HIIT in inpatient mental health settings. Trial registration ClinicalTrials.gov NCT03959735 . Registered June 22, 2019.